Vehicle-assisted ligature decapitation: A case report and a review of the literature. (July 2019) - Marchand, E.; Mesli, V.; Le Garff, E.; Pollard, J.; Bécart, A.; Hédouin, V.; Gosset, D.
Abstract: Decapitation resulting by vehicle-assisted ligature strangulation is a suicide method rarely described in the literature. The lesions observed at autopsy have a common morphology with to those found in post-hanging decapitation. They depend on the force applied by the acceleration of the vehicle, the slope of the road and the characteristics of the link used. They can also mimic a stabbing homicide. We report the case of a 43-year-old man who used a long steel rope, attached between his neck and a streetlight, and started his vehicle, causing a complete decapitation. The results of the autopsy provided information on the morphology of the cervical lesions, but also on the causes of death. In spite of decapitation, the histological examination of the organs confirmed the presence of asphyxiation process by a mechanical origin that occurred before decapitation. Highlights: Decapitation secondary to strangulation by vehicle-assisted ligature is uncommon in forensic medicine. The lesions observed at autopsy have a common morphology with to those found in post-hanging decapitation. The presence of asphyxiation process by a mechanical origin that occurred before decapitation.